1968
DOI: 10.1104/pp.43.5.747
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of the Dual Isotherm for Ion Absorption in Beet Tissue

Abstract: Abstract. Beet discs aged in 0.5 mM CaS04 develop a capacity to absorb K+ and Cl-from solutions of low concentration. The initial influx of these ions is described by a hyperbolic relationship with concentration in the range 0.01 to 0.5 mM KCI, which is identical with the system 1 absorption isotherm found in other tissues. A second hyperbolic isotherm, attributable to system 2, i's found at higher concentrations (1-50 mm Ka).When the transport of labeled ion to the vacuole is studied by wash-exchanging the bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
44
0

Year Published

1969
1969
2001
2001

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 22 publications
(29 reference statements)
2
44
0
Order By: Relevance
“…Such an observation would seem to be easily explained by assuming that the second mechanism (operating at Na concentration higher than 1 meq/liter) is not active in Na absorption during early stages of growth (3). The characteristics of ion absorption can change considerably under artificial conditions, i.e., aging (10,15). Rains (15) reported that in freshly sliced bean stem tissue, mechanisms 1 and 2 operate for Na absorption; when the tissue is aged, Na transport is mediated only by mechanism 2. The inability of the second mechanism to absorb Na during the early period of growth could be due to the lack of Na transport to the shoots until the plants are beyond the 10-leaf stage.…”
Section: Resultsmentioning
confidence: 99%
“…Such an observation would seem to be easily explained by assuming that the second mechanism (operating at Na concentration higher than 1 meq/liter) is not active in Na absorption during early stages of growth (3). The characteristics of ion absorption can change considerably under artificial conditions, i.e., aging (10,15). Rains (15) reported that in freshly sliced bean stem tissue, mechanisms 1 and 2 operate for Na absorption; when the tissue is aged, Na transport is mediated only by mechanism 2. The inability of the second mechanism to absorb Na during the early period of growth could be due to the lack of Na transport to the shoots until the plants are beyond the 10-leaf stage.…”
Section: Resultsmentioning
confidence: 99%
“…These observations show that the exchange was specific, and suggest that metabolism of malate-14C was of minor importance, at least at 20. At 250 malate-14C was more rapidly exchanged from the tissue, as would be expected (3,19,21), but concurrent metabolisnm complicated the interpretation, as shown by changes in the specific activity of other acids (table II). The time curves for malate-14C exchange are shown, in figure 4.…”
mentioning
confidence: 81%
“…On the basis of this analysis, Pitman an,d Saddler suggested that the active transport of potassium occurs at the plasmalemma. Although active potassium uptake, as opposed to a diffusion process, is not firmly established for red beet, Osmond and Laties (9) have demonstrated a typical highatffinity uptake mechanisimi for potassitumr and chloride ions in this tissue, anid have given evidence that this uptake mechanism is located at the plasmalemnma.…”
mentioning
confidence: 92%
“…The present study investigates the na-ture of the potassium efflux across the plasmalemma of beet cells, at an external concentration (0.6 mM) such that uptake by the high-affiiity mechanism of salt accumulation is maximal while uptake by the lowaffinity mechanism is relatively slow ' (3,9).…”
mentioning
confidence: 99%